2012
DOI: 10.5433/1679-0359.2012v33n1p213
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade de sementes de palmeira jerivá pelo teste de Raios X

Abstract: ResumoA palmeira jerivá (Syagrus romanzoffiana (Cham.) Glassman) é a palmeira nativa mais cultivada no Brasil. Sua propagação é realizada sexuadamente, contudo existe carência de informações no processo de produção de mudas de qualidade. O objetivo desta pesquisa foi padronizar o teste de Raios X na avaliação da qualidade fisiológica de sementes da palmeira jerivá. Utilizou-se oito amostras de 25 sementes, que foram submetidas ao teste de Raios X no aparelho Raicenter RC 300 Plus T em vários tempos e intensida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…The percentage of full seeds of the three groups varied between 65 and 80.5% (Table 1). These values were higher than the ones found by Sturião et al (2012), when they evaluated the internal morphology of seeds of Syagrus romanzoffiana through the xray tests; these authors found around 60.5% of viable seeds (full). According to MAPA (2009), fruit-seeds or seeds classified as full or totally formed by the xray tests contain all the essential tissues for the germination and, because of this, they are considered viable.…”
Section: Resultscontrasting
confidence: 61%
“…The percentage of full seeds of the three groups varied between 65 and 80.5% (Table 1). These values were higher than the ones found by Sturião et al (2012), when they evaluated the internal morphology of seeds of Syagrus romanzoffiana through the xray tests; these authors found around 60.5% of viable seeds (full). According to MAPA (2009), fruit-seeds or seeds classified as full or totally formed by the xray tests contain all the essential tissues for the germination and, because of this, they are considered viable.…”
Section: Resultscontrasting
confidence: 61%
“…Seed germination percentages decrease to very low levels after storage under laboratory conditions, most likely due to loss of embryo vigor and deterioration caused by crystallization of lipids of the seed endosperm (Balesevic-Tubic et al 2010;Goudel et al 2013;Oliveira et al 2015). T h e r e f o r e , p r e s e r v a t i o n a n d c o n s e r v a t i o n o f S. romanzoffiana via orthodox seed storage methods is not feasible (Sturião et al 2012;Goudel et al 2013;Oliveira et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The radiographic imaging analysis technique has been used with success in several native forest species, including the seeds of Eugenia pleurantha (Masetto et al, 2007), Cecropia pachystachya Trec. (Pupim, Novembre, Carvalho, & Cicero, 2008), Cedrela fissilis (Masetto, Faria, & Queiroz, 2008), Tabebuia heptaphylla (Amaral, Martins, Forti, Cicero, & Marcos Filho, 2011), Xylopia aromatica (Socolowski, Cicero, & Vieira, 2011), and Syagrus romanzoffiana (Cham) Glassman (Sturião, Landgraf, & Rosa, 2012), and in the morphological characterization of embryos of Tecoma stans L. JUSS. ex KUNTH (Socolowski & Cicero, 2008), the measurement of internal free areas in seeds of Acca sellowiana (Silva, Sarmento, Silveira, Silva, & Cicero, 2013), and the viewing of the internal morphology of seeds of Terminalia argentea (Gomes et al, 2014 Given the scarcity of information on the internal morphology and the effects of desiccation on achenes of species in the genus Anacardium, the objective of this study was to verify the efficiency of X-ray testing in evaluating the morphology and viability of A. othonianum achenes subjected to desiccation.…”
Section: Introductionmentioning
confidence: 99%